Reformulasi domain hukum ideologi Pancasila oleh Badan Pembinaan Ideologi Pancasila - Ferry Anggriawan (University of Merdeka Malang, 2020)
The promulgation of Presidential Regulation No. 7 of 2018 concerning the Pancasila Ideology Development Agency automatically results in the legal status of the Pancasila Ideology not only as the basis of the state, but as a state ideology that was ratified through Presidential Regulation No. 7 of 2018 concerning the Pancasila Ideology Development Agency. The legal facts that occur are legal vacancies related to the substance of the ideology's legal domain regulation. The result is that the Pancasila Ideology Development Board (BPIP) which has been given the authority to foster the community in relation to the Pancasila ideology, is not given a legal basis in terms of the ideological substance to be conveyed. Reformulation of the regulation of Pancasila ideology substance is very much needed in this matter, on the one hand it guarantees legal certainty over its legal domain, on the other hand ideology must be applied in accordance with historical roots, philosophies and positive laws that exist in Indonesia.How to cite item: Anggriawan, F. (2020). Reformulasi domain hukum ideologi Pancasila oleh Badan Pembinaan Ideologi Pancasila. Jurnal Cakrawala Hukum, 11(1), 31-40. doi:https://doi.org/10.26905/idjch.v11i1.4045